Analysis of eosinophil and lymphocyte concentrations on the incidence of mild and severe acute asthma exacerbations. - Humaidy, Raihan Syarif; Subkhan, Mohammad; Yuliyanasari, Nurma; Ambar, Nabil Salim (Gaceta Médica de Caracas, 2021)
Introduction: Exacerbation of asthma is an episode characterized by an increase in symptoms of progressive shortness of breath, coughing, wheezing, chest tightness, and a progressive decrease in lung function. Among the cells involved and activated in acute exacerbations in asthma are eosinophils and lymphocytes.